Aging population and the accessibility of public transportation services: policy perspective for Turkey - Sahin, Süleyman Nurullah Adahi; Özden, Abdulkadir; Faghri, Ardeshi; Vaughan, Michael L. (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Projections indicate that elderly individuals will constitute approximately 25% of the total population within the next 30 years. As aging and mobility-challenged populations require targeted planning, policies and physical infrastructure related to public transportation must be reassessed with greater precision and inclusivity. This study offers a comprehensive evaluation of Turkey’s national public transportation accessibility policies and explores their potential relevance for other countries. Additionally, interviews with four leading NGOs in Turkey were conducted to identify practical challenges faced by the elderly in urban transport systems. Thematic analysis of the feedback revealed critical deficiencies in vehicle design, fare policy, pedestrian infrastructure, traveler information systems, and driver behavior. Based on this multi-source analysis, the study proposes actionable policy recommendations to improve the accessibility, safety, and usability of public transportation services for elderly populations. The findings underscore the need for standardized design, stronger policy enforcement, and more inclusive digital and physical mobility solutions to ensure active aging and social participation.